The Auditor’s Opinion and Information Quality Communication / การแสดงความเห็นของผู้สอบบัญชีและการสื่อสารคุณภาพของข้อมูล - กนกอร แก้วประภา, ยุพดี ศิริวรรณ, เพ็ญศิริ คาจันทร์ษา และอลิสา กี่กระโทก, Kanok-on Kaewprapa, Yupadee Siriwan, Pen (Journal of Community Development Research (Humanities and Social Sciences); Vol 6 No 2 (2556): July - December 2013, 2014)
การแสดงความเห็นของผู้สอบบัญชี เปรียบเสมือนการส่งสัญญาณเตือนภัยเกี่ยวกับคุณภาพของข้อมูลในงบการเงินให้กับผู้ใช้ งบการเงินผ่านรูปแบบรายงานของผู้สอบบัญชี ซึ่งมี 4 ประเภท คือ ไม่มีเงื่อนไข, มีเงื่อนไข, ไม่แสดงความเห็น และงบการเงินไม่ถูกต้อง ดังนั้น วัตถุประสงค์ของงานวิจัยนี้ เพื่อศึกษาความแตกต่างของการสื่อสารคุณภาพของข้อมูลแยกตามรูปแบบการแสดงความเห็นของผู้สอบบัญชี โดยเก็บข้อมูลจากบริษัทจดทะเบียนในตลาดหลักทรัพย์ในกลุ่มอุตสาหกรรมบริการ จานวน 64 บริษัท ในช่วงปี พ.ศ. 2554-2555 ผลการศึกษา พบว่า การแสดงความเห็นของผู้สอบบัญชีแบบไม่มีเงื่อนไขจะสื่อสารคุณภาพของข้อมูลที่สูงกว่าการแสดงความเห็นของผู้สอบบัญชีในรูปแบบอื่นอย่างมีนัยสาคัญทางสถิติ ณ ระดับ 0.05 ดังนั้น ผลการศึกษาในเชิงประจักษ์ยืนยันได้ว่า การแสดงความเห็นของผู้สอบบัญชีสามารถสะท้อนคุณภาพของข้อมูลได้สอดคล้องกับมาตรฐานการสอบบัญชี รหัส 700 เรื่อง รายงานของผู้สอบบัญชีต่อ งบการเงิน ซึ่งเป็นผลให้รายงานของผู้สอบบัญชียังสามารถนามาใช้เป็นเครื่องมือในการส่งสัญญาณเตือนภัยเกี่ยวกับการจัดการกาไรหรือการตกแต่งบัญชีแก่ผู้ใช้งบการเงินได้ คำสำคัญ: รายงานของผู้สอบบัญชี การแสดงความเห็นของผู้สอบบัญชี คุณภาพข้อมูล The auditor’s opinion acts as an alarm informing the information quality in financial statements to users via the auditor’s report which there are 4 types consisting of the unqualified opinion, the qualified opinion, the disclaimer of opinion, and the adverse opinion. Therefore, the objective of this research is to examine the difference of communicating the information quality divided by the auditor’s opinion types. The listed firms of service industry in the Stock Exchange of Thailand (SET), totally 64 firms, were chosen as the population and sample during the period 2011 – 2012. The result showed that the auditor’s report with unqualified opinion can significantly communicate the higher level of information quality than those with other opinions at a significance of 0.05 levels. Thus, the empirical result confirmed that the auditor’s opinion can communicate the information quality in accordance with Thai audit standard (ISA) 700 “the auditor’s report on financial statements” and the auditor’s report can be the warning on earnings management or creative accounting to users. Keywords: Auditor’s Report Forms, Auditor’s opinion, Information Quality
Keywords: รายงานของผู้สอบบัญชี การแสดงความเห็นของผู้สอบบัญชี คุณภาพข้อมูล Auditor’s Report Forms, Auditor’s opinion, Information Quality